PENGARUH SOSIALISASI PERPAJAKAN, KUALITAS PELAYANAN FISKUS, PEMAHAMAN TENTANG PERATURAN PERPAJAKAN DAN PENERAPAN E-FILING TERHADAP KEPATUHAN WAJIB PAJAK (Studi Kasus pada Wajib Pajak Orang Pribadi UMKM di Kantor Pelayanan Pajak Pratama Pekanbaru Senapelan) - Zirman Zirman; Devi Safitri (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2018)
This study aimed to examine the effect of tax socialization, the quality of tax service, the understanding of taxation regulations, and the application of e-filing to the compliance of taxpayers of individuals of UMKM registered in KPP Pratama Pekanbaru Senapelan. Background problem in this research is still low compliance of taxpayer to entrepreneur of UMKM. Techniques in sampling using probability sampling with simple random sampling method and using slovin formula. Of the 100 questionnaires distributed, only 88 questionnaires can be processed. Data analysis technique used is multiple regression analysis and coefficient of determination processed with SPSS version 20. The results showed that the socialization of taxation, the quality of tax service, the understanding of tax regulations, and the application of e-Filing affect simultaneously to taxpayer compliance. This can be seen from the value of F arithmetic > F table (18.433 > 2.46). Partially, the socialization of taxation and application of eFiling has a significant effect on taxpayer compliance. While the quality of fiscal services and the understanding of tax regulations have no significant effect on taxpayer compliance. The result of determination coefficient (R2 ) shows that the overall ability of independent variable to influence the dependent variable is 44,5%. While the remaining 55.5% influenced by other variables not included in this study.Keywords : taxpayer compliance, tax socialization, fiscal service quality, understanding of tax regulations, e-Filing application